Julien Offray de La Mettrie, 'Discours sur le bonheur' - Falvey, J (Voltaire Foundation, 2017)
INTRODUCTION I. Principles of this edition i. The text ii. Dates iii. Presentation iv. Structure of the Discours sur le bonheur II. Reflections of contemporaries in the writing and the rewritings i. Maupertuis and his friend ii. Maupertuis and 'la philosophie morale' iii. Fontenelle iv. Madame Du Châtelet v. Frederick II vi. Pernetti vii. 'Saint-Evremond' (La Serre) III. Discours sur le bonheur in relation to some earlier figures i. Descartes ii. Montaigne iii. Seneca: epicureanism and stoicism iv. Other figures referred to by La Mettrie IV. Reverberations i. La Mettrie's personality ii. Exploitation of La Mettrie by religious writers iii. Sensitivity of the philosophes to exploitation of La Mettrie iv. Reaction to La Mettrie in periodicals V. Conclusion THE TEXT Preface Section i. Introductory passage Section ii. Le bonheur organique Section iii. Education Section iv. Fortitude Section v. Happiness through social facilities Section vi. The medical standpoint Section vii. Endings Appendixes